The Mediating Effect of Negative Appearance Evaluation on the Relationship Between Eating Attitudes and Sociocultural Attitudes Toward Appearance - Wang, Ruohang; Gan, Youteng; Wang, Xueyu; Li, Jianye; Lipowska, Małgorzata; Izydorczyk, Bernadetta; Guo, Shuai; Lipowski, Mariusz; Yang, Yin; Fan, Hongying (Frontiers in Psychiatry, 2022)
Objective Body-image disturbance and eating disorders are significant physical and mental health problems in China. Attitudes toward the body are thought to work in conjunction with other established risk factors for dietary pathology, which include body dissatisfaction, dieting, and negative effects. Negative appearance evaluation may be valuable for extending our understanding of measuring factors and potential causal relationships associated with body image and eating problems. Therefore, this study aimed to determine the association between negative appearance evaluation and a combination of eating attitudes and sociocultural attitudes toward appearance and the mediating effect of negative appearance evaluation on the relationship between eating attitudes and sociocultural attitudes toward appearance. Methods We invited 339 Chinese adults to undergo the Eating Attitudes Test (EAT-26), the Fear of Negative Appearance Evaluation Scale (FNAES), and the Sociocultural Attitudes toward Appearance (SATAQ-3) scale, and used AMOS 24.0 for model construction and mediating effects testing. Results There was a significant positive correlation between EAT-26 scores and FNAES (p < 0.001) and SATAQ-3 scores (p < 0.001), and all dimensions except internalization general were significantly positively correlated (p < 0.05). There was a significant positive correlation between FNAES and SATAQ-3 scores for all dimensions (p < 0. 01). There was no significant direct effect of eating attitude on sociocultural attitude toward appearance; however, there was a significant mediating effect of fear of negative appearance evaluation. Conclusion Our results demonstrate that negative appearance evaluation fully mediates the relationship between eating attitudes and sociocultural attitudes toward appearance. An individual’s attitude toward eating affects negative body perceptions and thus their perception of their own body shape. Our exploration of the specific effects of eating attitudes on body perception provides a psychological basis for guidance and developing interventions regarding attitudes toward the body.